Health Related Quality of Life in patients undergoing Lower Limb Amputation secondary to Peripheral Arterial Disease - Rubina Hashim, Zarmina Islam, Waryam Panhwar, Ziad Sophie, Fahad Tariq Berlas, Areeba Salim (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess domains of health-related quality of life among patients undergoing major lower limb amputation secondary to peripheral arterial disease. Study design: Observational questionnaire-based study. Place and Duration: Data from 1st January to 31 December 2020(collected from September 2022 to November 2022) was assessed out of which ninety-one patients fulfilled the inclusion criteria. Methodology: Twenty-three patients were interviewed after verbal consent over telephone using validated questionnaires: World Health Organization Quality of Life-BREF, Amputee Single Item Mobility Measure, Locomotor Capability Index-5. Independent sample t-tests and ANOVA were performed for demographics and domain scores. Pearson-Correlation tests were performed for relations between domains and mobility scores. Results: 12 (52.20%) of interviewed patients received below knee amputation, comprising mostly of males 16 (69.60%) with diabetes 18 (78.30%). Participants who used prosthesis had statistically significantly greater mobility scores compared to non-prosthesis users t(21)=3.396, p=0.03. Below knee amputees report better quality of life compared to above knee as these amputees had lower physical domain (mean difference -22.75, p=0.027) and environmental domain scores (mean difference -12.44, p=0.009). This study found that male participants had statistically significantly greater physical t(21)=2.698, p=0.013 and environmental t(21)=2.77,1 p =0.011 scores after a major lower limb amputation compared to females. Conclusion: Males and patients with prosthesis report significantly better quality of life compared to females and non-prosthesis users, owing to socioeconomic and cultural barriers. Keywords (MeSH): Amputation, Surgical, peripheral arterial disease, Artificial Limbs, Quality of Life